Additive effects of warming and nitrogen addition on the performance and competitiveness of invasive Solidago canadensis L. - Ren, Guangqian; Yang, Bin; Cui, Miaomiao; Yu, Haochen; Fan, Xue; Dai, Zhicong; Sun, Jianfan; Li, Guanlin; Zhang, Haiyan; Du, Daolin (Frontiers in Plant Science, 2022)
Changes in temperature and nitrogen (N) deposition determine the growth and competitive dominance of both invasive and native plants. However, a paucity of experimental evidence limits understanding of how these changes influence plant invasion. Therefore, we conducted a greenhouse experiment in which invasive Solidago canadensis L. was planted in mixed culture with native Artemisia argyi Levl. et Van under combined conditions of warming and N addition. Our results show that due to the strong positive effect of nitrogen addition, the temperature increases and nitrogen deposition interaction resulted in greatly enhanced species performance. Most of the relative change ratios (RCR) of phenotypic traits differences between S. canadensis and A. argyi occur in the low invasion stage, and six of eight traits had higher RCR in response to N addition and/or warming in native A. argyi than in invasive S. canadensis. Our results also demonstrate that the effects of the warming and nitrogen interaction on growth-related traits and competitiveness of S. canadensis and A. argyi were usually additive rather than synergistic or antagonistic. This conclusion suggests that the impact of warming and nitrogen deposition on S. canadensis can be inferred from single factor studies. Further, environmental changes did not modify the competitive relationship between invasive S. canadensis and native A. argyi but the relative yield of S. canadensis was significantly greater than A. argyi. This finding indicated that we can rule out the influence of environmental changes such as N addition and warming which makes S. canadensis successfully invade new habitats through competition. Correlation analysis showed that invasive S. canadensis may be more inclined to mobilize various characteristics to strengthen competition during the invasion process, which will facilitate S. canadensis becoming the superior competitor in S. canadensis-A. argyi interactions. These findings contribute to our understanding of the spreading of invasive plants such as S. canadensis under climate change and help identify potential precautionary measures that could prevent biological invasions.